Cross-cultural comparison of food appetite and restaurant features - Islam, Md Sami Ul; Abib, Md. Shariful Huq (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.